Journal editors should be productive role models - Subrata, Sumarno Adi; Phuphaibul, Rutja (Innovation in Health for Society, 2025)
In the evolving landscape of academic publishing, the role of journal editors extends beyond mere gatekeeping; they are pivotal in shaping the integrity and productivity of scholarly discourse. This editorial explores the imperative for journal editors to embody the qualities of productive role models within their respective fields. Demonstrating effective time management, ethical decision-making, and a commitment to continuous learning can inspire authors, reviewers, and the broader academic community. The editorial highlights key attributes that define productive role models, including transparency in editorial processes, responsiveness to feedback, and the promotion of diverse perspectives in published research. Furthermore, it emphasizes the importance of mentorship, where editors actively engage with emerging scholars, fostering an inclusive environment that encourages innovation and collaboration. Adopting these practices not only enhance the quality of their publications but also contribute to a culture of excellence in research. This editorial advocates for a shift in the perception of editorial roles, positioning editors as leaders who champion productivity and ethical standards in academia. Ultimately, this perspective underscores the significance of editorial influence in shaping the future of scholarly publishing, encouraging a more dynamic and responsible approach to knowledge dissemination. Keywords: Academic publication; journal editor; scientific contribution; healthcare science; role models